Developing a strategy for the national coordinated soil moisture monitoring network. Issue 4 (8th June 2021) - Cosh, Michael H.; Caldwell, Todd G.; Baker, C. Bruce; Bolten, John D.; Edwards, Nathan; Goble, Peter; Hofman, Heather; Ochsner, Tyson E.; Quiring, Steven; Schalk, Charles; Skumanich, Marina; Svoboda, Mark; et al.
Abstract: Soil moisture is a critical land surface variable, affecting a wide variety of climatological, agricultural, and hydrological processes. Determining the current soil moisture status is possible via a variety of methods, including in situ monitoring, remote sensing, and numerical modeling. Although all of these approaches are rapidly evolving, there is no cohesive strategy or framework to integrate these diverse information sources to develop and disseminate coordinated national soil moisture products that will improve our ability to understand climate variability. The National Coordinated Soil Moisture Monitoring Network initiative has developed a national strategy for network coordination with NOAA's National Integrated Drought Information System. The strategy is currently in review within NOAA, and work is underway to implement the initial milestones of the strategy. This update reviews the goals and steps being taken to establish this national‐scale coordination for soil moisture monitoring in the United States. Core Ideas: Soil moisture is a critical yet underrepresented land surface variable. Soil moisture data collection is undergoing rapid growth and innovation. We present a strategy for a nationally coordinated monitoring network.